Insolvency and financial health prediction model for the listed companies on the Indonesia Stock Exchange - Khaira Amalia Fachrudin (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2021)
An insolvency and financial health prediction model is an important warning to decision-makers. This study aims to design a model that provides numbers and ranges for prediction of company insolvency and financial health. The study population is all the listed companies on the Indonesia Stock Exchange, while the sample consists of 216 companies that had negative equity from 2010 to 2019 and 216 companies with positive equity. The independent variables include the solvency and profitability ratios in one and two years before the insolvency. Logistic regression was used as an analysis tool. The results are 24 prediction models. The comprehensive one revealing the solvency ratio in the previous one year and the profitability ratio in the previous one and two years can predict the probability of insolvency and financial health.